A contribution to the sociological study of population - Stanojević, Nenad (Sociološki pregled, 2022)
The paper presents a review of the textbook Population in the Sociological Context by Professor Suzana Marković Krstić, PhD. At the beginning, the importance of the sociological study of population is indicated, as well as the necessity of multidisciplinary and interdisciplinary approaches in studying this topic. Then the structure of the textbook is given, with the analysis of the key matters of the sociological study of population the author deals with.
Keywords: population; sociology; demographics; socio-demographics; demographic and social development